2010
DOI: 10.3109/09638288.2010.490867
|View full text |Cite
|
Sign up to set email alerts
|

Physical impairment, depressive symptoms and pre-stroke fatigue are related to fatigue in the acute phase after stroke

Abstract: Pre-stroke fatigue and fatigue during the acute phase needs to be assessed in relation to physical functioning and depression during recovery and the rehabilitation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
157
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(177 citation statements)
references
References 40 publications
19
157
1
Order By: Relevance
“…25 It is likely that fatigue is multidimensional in its aetiology, sometimes linked to limited aerobic capacity, depression, stroke location, and/or comorbid conditions as well as to stroke. 22,24,26 Despite the prevalence and importance of fatigue, there is a dearth of research on post-stroke fatigue interventions. A recent systematic review 27 found only two small drug trials and one self-management intervention study, none of which found a benefit of the experimental intervention over the control.…”
Section: Fatigue and Fitness Levelmentioning
confidence: 99%
“…25 It is likely that fatigue is multidimensional in its aetiology, sometimes linked to limited aerobic capacity, depression, stroke location, and/or comorbid conditions as well as to stroke. 22,24,26 Despite the prevalence and importance of fatigue, there is a dearth of research on post-stroke fatigue interventions. A recent systematic review 27 found only two small drug trials and one self-management intervention study, none of which found a benefit of the experimental intervention over the control.…”
Section: Fatigue and Fitness Levelmentioning
confidence: 99%
“…The Fatigue Severity Scale-7 (FSS7) [21] is a wellvalidated tool to assess fatigue impact. It contains the last 7 items of the original 9-item FSS [31], to be scored on a 7-point Likert Scale.…”
Section: Methodsmentioning
confidence: 99%
“…It contains the last 7 items of the original 9-item FSS [31], to be scored on a 7-point Likert Scale. A mean score was calculated and a higher score than 5 indicated severe fatigue impact (range: 1-7) [21,31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although OSA was not specifically assessed in our study, we previously reported that fatigue during the acute phase was not associated with either the Pittsburgh Sleep Quality Index 6 or actigraph estimates of nighttime sleep disturbance. 7 Thus, it seems unlikely that the fatigue patients experienced during the acute phase was solely attributable to sleep disturbance.…”
Section: Supply and Demand Analysis Of The Current And Future Us Neurmentioning
confidence: 99%